Effect of Sterilization Time and Temperature Stability on Free Fatty Acid Formation in Crude Palm Oil: Implications for Sterilizer Asset Performance - Rizka Nurjanah; Arief Panca Putra; Bagus Nugroho; Elita Nurfitriyani Sulistyo; Subakho Aryo Saloko; Agus Manto (Tropical Plantation Journal, 2026)
This study investigated the effect of the sterilization time of Fresh Fruit Bunch (FFB) on the Free Fatty Acid (FFA) content in Crude Palm Oil (CPO). It evaluated its implications for sterilization asset performance. A laboratory-scale experiment was conducted using a manual steam sterilizer heated by a gas stove, resulting in fluctuating sterilization temperatures. Three sterilization durations (30, 45, and 60 min) were tested, each with two replicate groups. Crude oil was extracted using a hydraulic press, and FFA content was determined using alkali titration 0.2 N NaOH and phenolphthalein indicator. The results showed considerable variation in FFA content among treatments. The lowest FFA value (2.50%) was obtained in the 60-min treatment and was the only result that complied with the Indonesian National Standard (SNI 01-2901-2006), which limits FFA content to 5.00%. In contrast, the highest FFA values reached 13.13% and 13.30% in the 45-min and 60-min treatments, respectively. These findings indicate that temperature instability during sterilization had a greater impact on FFA formation than sterilization duration. From an asset management perspective, sterilization equipment is a critical asset whose operational performance directly influences product quality. Therefore, maintaining stable sterilization temperatures is essential for minimizing FFA formation and ensuring consistent CPO quality.